Application of Lai and Juang Methods for Liquefaction Probability Analysis in Petobo, Palu - Nia Dwi Ariyanti; Galuh Chrismaningwang; Yusep Muslih Purwanai; Raden Harya Dananjaya (Media Teknik Sipil, 2024)
Liquefaction is a phenomenon where the soil loses its strength and rigidity, rendering it unable to support structures, often triggered by seismic activity. In Petobo, Palu City, a 7,4 magnitude earthquake caused significant subsidence and casualties, underscoring the area's susceptibility to liquefaction. This study investigates the liquefaction potential in Petobo using N-SPT data and evaluates the probability of liquefaction based on Factor of Safety (FS) values. The analysis employs probabilistic methods by Lai et al. (2006) and Juang et al. (2008), using an empirical approach based on FS. Results from six test points (LP-1 to LP-6) reveal that liquefaction potential exists at LP-2, LP-4, and LP-5, with varying risks influenced by the earthquake's magnitude. LP-5 demonstrates a high liquefaction potential, with a Liquefaction Potential Index (LPI) between 4 and 15 across different seismic magnitudes. Additionally, LP-5 shows a high probability of liquefaction, with the Lai method indicating "Almost Certainly Liquefied" at 0,99, while the Juang method suggests "Not Likely to Liquefy" at 0,32. The findings highlight that higher earthquake magnitudes significantly increase LPI values and liquefaction probabilities, emphasizing the importance of seismic considerations in the region.